PDBsum additions - de Beer, Tjaart A P; Berka, Karel; Thornton, Janet M; Laskowski, Roman A (Nucleic acids research, 2014)
PDBsum, http://www.ebi.ac.uk/pdbsum, is a website providing numerous pictorial analyses of each entry in the Protein Data Bank. It portrays the structural features of all proteins, DNA and ligands in the entry, as well as depicting the interactions between them. The latest features, described here, include annotation of human protein sequences with their naturally occurring amino acid variants, dynamic graphs showing the relationships between related protein domain architectures, analyses of ligand binding clusters across different experimental determinations of the same protein, analyses of tunnels in proteins and new search options.
Keywords: shluková analýza; počítačová grafika; Cluster Analysis; Humans; Protein Structure, Tertiary; genetická variace; Proteins; Protein Conformation; Drug Design; konformace proteinů; Ligands; Internet; proteiny; ligandy; databáze proteinů; internet; Genetic Variation; lidé; Databases, Protein; racionální návrh léčiv; Computer Graphics; terciární struktura proteinů